Gestión por procesos y la productividad laboral de los trabajadores de la Municipalidad Distrital de Punchana 2025 - Valderrama Chavez, Frank Jackson (2025)
The purpose of this research was to determine the relationship between process management and labour productivity in the workers of the District Municipality of Punchana 2025. Opting for a basic study with a non experimental cross-sectional design, the sample consisted of 55 workers for the survey conducted with a questionnaire for data collection. The findings show that process management is very good (45.5%) and labour productivity is rated as good (50.9%). Therefore, it is determined that there is a significant relationship between the variables (p=0.000). Likewise, the strategy processes dimension shows a significance of p=0.010; the business processes dimension shows a significance of p=0.040; finally, the support processes dimension shows a significance of p=0.020), these dimensions are significantly related to labour productivity.